The Influence of Fuel Injection Pressure on Engine Performance and Smoke Emissions in a Diesel Engine Using Palm Oil Biodiesel Blend Fuel - Irlido Irwansyah; Dori Yuvenda; Yolli Fernanda; Durain Parmanoan (Jurnal Vokasi Mekanika (VoMek), 2026)
This study was conducted to examine the effect of fuel injection pressure variations on diesel engine performance and Smoke Emissions in Yanmar TF105MR-DI diesel engines using B50 palm oil biodiesel mixture. The test was conducted at injection pressures of 210, 220, 230, and 240 kg/cm² with load variations of 1000, 2000, 3000, and 4000 W. Parameters observed included power, torque, Specific Fuel Consumption (SFC), thermal efficiency, and exhaust gas turbidity level as indicators of Smoke Emissions. The test results show that the change in injection pressure has an effect on the combustion process and the performance characteristics of the engine. An increase in injection pressure to 230 kg/cm² is able to improve the fuel atomization process so that the formation of the air-fuel mixture becomes more homogeneous. This results in higher power and torque than other pressure variations, along with a decrease in SFC values and increased thermal efficiency at all levels of load. However, when the injection pressure is increased to 240 kg/cm², the performance of the engine tends to decrease. This is suspected to be caused by the penetration of the fuel spray too far so that the mixing and combustion process does not take place optimally. In terms of emissions, a more optimal injection pressure also contributes to a reduction in the turbidity level of exhaust fumes.